Efficient carbon capture for coal power plants - Scherer, V., ....-; Stolten, Detlef, ....- (Weinheim : Wiley, 2011)
The book addresses the interdisciplinary character of power plant technology. It focuses on power plant technology and ways to improve the effciency of CCS technology. Consequently, process engineers as well as chemists, physicists and materials' engineers are addressed. The book delivers specific insights for scientists and engineers in their field as well as enough overview for them to understand the opportunities and implications of the other disciplines. The books details the three principal ways to capture CO2 produced in power plants: Oxyfuel combustion, Postcombustion and Precombustion. The main part of the book focuses on the different approaches to remove carbon dioxide - i.e. the absorption processes and the membrane processes will first be explained from the physical, chemical and materials point of view in order to lay the foundation for the subsequent technical processes and to reduce the complexity of the information provided
Keywords: Kerncentrales ; kernenergie